Normotensive cardiomyopathy and malignant hypertension in phaeochromocytoma. Issue 676 (February 1982) - Shapiro, L. M.; Trethowan, N.; Singh, S. P.
Abstract : A patient with two different presentations of phaeochromocytoma is described. She initially presented with normal blood pressure and heart failure following a prolonged feverish prodrome. A provisional diagnosis of myocarditis or early congestive cardiomyopathy was made and she improved with digoxin and diuretics. Eighteen months later, after a period of normotension free from heart failure, she developed malignant hypertension with recurrence of heart failure. A phaeochromocytoma was surgically removed, with return to normal of blood pressure and cardiac status. It would seem that the initial presentation of the phaeochromocytoma was a catecholamine-induced myocarditis without hypertension and this resolved with the subsequent development of malignant hypertension. The possible mechanisms responsible for this are discussed and it is concluded that phaeochromocytoma should be considered in patients who have heart failure and persistent features of myocarditis.